Challenges and Solutions of Solid‐State Electrolyte Film for Large‐Scale Applications - Huang, Xiaozhong; Li, Tao; Fan, Weiwei; Xiao, Rui; Cheng, Xin‐Bing (Advanced energy materials, 2024)
Solid‐state lithium‐ion batteries are widely accepted as the promising next‐generation energy storage technology due to higher energy density and improved safety compared to conventional lithium‐ion batteries with liquid electrolytes. Large‐area solid‐state electrolyte (SSE) films with adequate thickness control, improved ionic conductivity, and good interfacial contact can reduce internal resistance, increase the real energy density of batteries, and reduce manufacturing costs. Optimization of SSE properties at the particle scale and large‐scale preparation of SSE films are key to the development of high‐performance solid‐state lithium‐ion batteries and their industrialization. Therefore, this paper provides a comprehensive review of SSE, covering both particle‐level features like the effects of particle size, density, and air stability on the electrochemical performance, as well as four major routes for large‐scale preparation and relevant strategies for structural optimization of SSE films. In addition, the effects of large‐area SSE films on the electrochemical performance of solid‐state batteries and their applications in pouch solid‐state lithium‐ion battery systems are discussed in detail. Finally, the design principles of SSE particles and SSE films are summarized and the development direction of thin SSEs is envisaged. In this paper, the effects of SSE on the electrochemical performance of batteries at the particle scale and optimization strategies, followed by four mainstream and other methods for large‐area preparation of SSE films are introduced. The aim is to provide a comprehensive overview of SSE film design and to promote the development of solid‐state batteries.